Digital Transformation in Case Handling: A Juridical Review of Technology Utilization in the Justice System in Indonesia and Malaysia - Ulfah Dwi Rahmawati; Arief Budiono; Fahmi Fairuzzaman; Ahmad Shamsul Abd Aziz (Unnes Law Journal, 2024)
Indonesia and Malaysia have different judicial systems, given that they differ in applying the legal system. However, Indonesia and Malaysia have implemented digitalization in the judicial process from the earliest to the final stages. The use of technology is an effort to reform and digitize to achieve modern justice that is fast and efficient while still upholding legal norms. The objectives of this research are: (1) To find out what forms of technology utilization are in the judicial system in Indonesia and Malaysia and (2) To find out how the law views and regulates this based on applicable Legislation. The writing that was written using the normative juridical method based on a literature study found that the use of technology is desired by the law as evidenced by Legislation governing digitization. The two countries' regulations still require much improvement and evaluation, both substantively and in implementation, to achieve the main objectives.